Research on beam management of non-coaxial OAM communication system - Feng ZHENG; Gaoming DUAN; Liangang CHI (Dianxin kexue)
As a new modulated degree of freedom, orbital angular momentum (OAM) could greatly improve the spectrum utilization of wireless communication.However, the uniform circular array (UCA)-based OAM communication system requires the transceiver array to be static and perfectly aligned, which makes it difficult for OAM to be practically applied.A beam management method based on OAM was proposed, which determined the best beam matching by scanning the beam of receiver and receiver, and the matched beam was used to communicate.Simulation results show that the proposed scheme could effectively reduce the system performance degradation caused by non-coaxial of receiver and transmitter arrays.